An experimental study to investigate the role of pyrolysis reaction on in-situ hydrogen generation from sandstone oil reservoirs - Mohamed Abdalsalam Hanfi; Olalekan Saheed Alade; Abdulkadir Tanimu; Mohamed Mahmoud; Sulaiman A. Alarifi (Petroleum, 2025)
In-situ combustion gasification (ISCG) is a technology in the field pilot stage used for hydrogen generation from oil reservoirs. ISCG is implemented by injecting an oxidant (pure oxygen, air, …) into the reservoir to trigger in-situ chemical reactions responsible for hydrogen generation. Pyrolysis reaction is one of the significant reactions triggered by in-situ combustion (ISC). This study used a fixed-bed micro-activity test (MAT) unit to investigate hydrogen generation from crude oil through pyrolysis. Crude oil pyrolysis experiments were conducted in the MAT unit under different temperatures (300 °C, 400 °C, 500 °C, 600 °C), atmospheric pressure, and under a flow of a nitrogen gas. The results showed that the threshold initiation temperature of hydrogen generation and coke formation was about 500 °C. The experiments demonstrated that the introduced sandstone enhanced hydrogen generation and coke formation at high temperatures. The maximum volume of hydrogen generated with sandstone effect reached 8.15 mL at 600 °C, while that without sandstone was only 6.39 mL at 600 °C. The study provides deep insights into the in-situ hydrogen generation from crude oil through pyrolysis. In addition, the obtained data of various pyrolysis products provide a comprehensive representation of crude oil pyrolysis that could promote the existing reaction models of in-situ hydrogen generation from the gasification of crude oil. The findings demonstrate the potential of adopting pyrolysis of crude oil for direct hydrogen generation from reservoirs.